Разработка системы автоматической синхронизации исполнительных и регистрирующих устройств баллистической трассы - Бирюков, Илья Михайлович (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The article deals with the developed method for registration and automatic synchronization of the actuating devices of a ballistic track, which allows coordinating the execution units (photo/video equipment or strobe lights) with the moment a fast-moving body is found in the shooting area at a previously unknown muzzle velocity.